2021
DOI: 10.1180/mgm.2021.83
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy of Ga- and Ge-bearing metallurgical slags from Tsumeb, Namibia

Abstract: Gallium (Ga) and germanium (Ge) are technologically important critical elements. Lead blast furnace slags from Tsumeb, Namibia, comprise over two million metric tons of material that contains high levels of Ga (135–156 ppm) and Ge (128–441 ppm) in addition to significant Zn concentrations (up to 11 wt.%) and represent a potential resource for these elements. A combination of mineralogical and chemical methods (PXRD, FEG-SEM-EPMA and LA-ICP-MS) indicated different partitioning of Ga and Ge within the individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…[33] For recovery of those elements from slags the understanding of the partitioning of the elements between the phases available in slags is key. For example, the critical element Ga is found to be predominantly bound to Zn–Fe–Al spinels within lead blast furnace slags from Tsumeb, Namibia as reported by Ettler et al [35] Ni-containing spinel is observed in Ni converter slags by Yu and Chattopadhyay [36], which is relevant for metal loss in slag. The melting point of oxyspinels is usually higher than the process temperature of non-ferrous pyrometallurgical operation, so they occur in the slag as solid particles.…”
Section: Spinels As Part Of Slagsmentioning
confidence: 84%
“…[33] For recovery of those elements from slags the understanding of the partitioning of the elements between the phases available in slags is key. For example, the critical element Ga is found to be predominantly bound to Zn–Fe–Al spinels within lead blast furnace slags from Tsumeb, Namibia as reported by Ettler et al [35] Ni-containing spinel is observed in Ni converter slags by Yu and Chattopadhyay [36], which is relevant for metal loss in slag. The melting point of oxyspinels is usually higher than the process temperature of non-ferrous pyrometallurgical operation, so they occur in the slag as solid particles.…”
Section: Spinels As Part Of Slagsmentioning
confidence: 84%
“…Examples of materials from zinc metallurgy with elevated germanium concentrations include residues from hydrometallurgical processes obtained during the leaching of zinc ores and purification of zinc electrolytes [ 7 11 ]. In pyrometallurgical operations, such by-products as alloy and slag from lead blast furnaces [ 12 , 13 ], flue dust from flash copper smelting [ 14 ], polymetallic alloy from New Jersey process [ 15 ] or dust from fuming of leaching residue [ 16 18 ] may be generated. In subsequent stages, the Ge-bearing material is firstly leached, then germanium is selectively recovered from the solution by tannin precipitation, and cementation with iron or zinc powder, either by solvent extraction.…”
Section: Introductionmentioning
confidence: 99%